Qualitative agroclimatic assessment of rainfed crops (MAUSAM, 1990)
Meteorological drought is a natural disaster and it can adversely affect economy of a nation. In the present paper, two indices for drought assessment, namely, the Generalised Monsoon Index (GMI) and the Yield Moisture Index (YMI), have been discussed and as an example, their application to the assessment of kharif sorghum yields in the Dry Farming Region (DFR) of Maharashtra State has been presented. It is seen that YMI is a better indicator for assessing the drought impact. The Jaw magnitudes of the percentiles of the YMI agro climatic index occurring over the early successive cumulative periods of the monsoon rainfall season can be taken as an early warning of the adverse effect of drought on the crop and the consequent likely decrease in crop yield.